Evaluation the mechanical properties of medium density fiber board of domestic production and imported with help of vertical density profile, infrared rays, Spectroscopy and imagine analyses (case study of Arian Sina Co) - vahid moazami (Regional Information Center for Science and Technology (RICeST), 2017)
The aim of this study was evaluation the mechanical properties of medium density fiber board of domestic production of Iran Company and imported medium density fiber board (Malaysia). Due to lack of knowledge and lack of access_to information, factors and variables influencing in production of fiberboard papers in industry especially imported boards, to better understand the differences of infrared radiation to reveal a vertical density profile of boards and infrared Spectroscopy (FT_IR), to identify compounds of fibers and the links caused by adhesive and dimensional analysis of fibers of the boards were used. The results of statistical analysis showed that the boards of domestic production_than to the imported boards have high mechanical strength. So that average flexural strength and modulus of elasticity in order for boards constructed in the country 34.56 and 2762 MPa and 2277 MPa, and it is 24.87 for imported supplies. The average internal bond strength of boards manufactured domestically MPa 0.78 and 0.58 have been of imported for the board. The results of density profile showed that the boards made into the country, in middle layer have 599 up to 615 kg/ m3 density and also surface layers have 1060 kg/m3, while the imported boards in middle layer have 533 up to 571 kg/m3 density and also surface layers have 1020 kg/m3 density. According to the results obtained from FT_IR spectra’s of the samples. Domestic boards than to the imported boards have more hydrogen links. Beside, pictures of analysis of fibers showed that the highest, lowest and average of fibers length for the domestic boards 260, 10 and 120 and lowest and average of fibers length for the imported boards 190, 5 and 45 were obtained, respectively.